1996
DOI: 10.1007/bf02208593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandin E1 on ammonia concentration in blood of patients with hepatic resection

Abstract: Plasma concentrations of ammonia were examined following prostaglandin E1 (PGE1) administration in 16 patients who received hepatectomy for hepatocellular carcinoma. PGE1 at 0.01-0.04 microgram/kg/min was administered for approximately 24 hr during the perioperative periods. The ammonia concentration was reduced a day after the operation following intravenous administration of PGE1 in cirrhotic patients compared to noncirrhotic patients with or without PGE1 injection. Serum liver function scores, glutamic pyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There are several experimental9,10,22 or clinical2,12,38 reports on the effect of PGE 1 on ischemically injured liver or on hepatectomized liver. However, no combined study has yet been performed on the hemodynamic effect of intraportally administered PGE 1 in a model of ischemia reperfusion followed by partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several experimental9,10,22 or clinical2,12,38 reports on the effect of PGE 1 on ischemically injured liver or on hepatectomized liver. However, no combined study has yet been performed on the hemodynamic effect of intraportally administered PGE 1 in a model of ischemia reperfusion followed by partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoprotective effects of PGE 1 on ischemic liver damage have recently been demonstrated experimentally . Clinically, PGE 1 has been used to improve postoperative liver function in hepatectomized patients as well as to treat primary non‐function after transplantation of the liver with apparent success …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that increasing blood flow to the liver during reperfusion is one of the essential factors for a good prognosis [2]. Prostaglandin E 1 (PGE 1) has been used extensively for cytoprotection against various damaging agents both experimentally [3,4] and clinically in hepatectomized patients [5,6]. It has been used in noncirrhotic livers as well as to treat primary nonfunction after liver transplantation [7,8] with apparent success.…”
mentioning
confidence: 99%